POETRY ART OF TABIBIY - Nurmamatova Aziza (International Journal of Literature and Language Studies, 2026)
This article examines the genre diversity of Ahmad Tabibi’s literary heritage in the Turkic language and analyzes the distinctive features of his poetic artistry. Special attention is paid to the tuyuq and rubai genres, which vividly demonstrate the poet’s artistic mastery. Through textual analysis, the study reveals the use of tajnis (paronomasia), metaphor, symbolism, and Sufi imagery in Tabibi’s tuyuqs. Furthermore, the article explores the philosophical and lyrical themes reflected in his rubais, including the transience of life, separation, love, and spiritual experiences. The research concludes that Ahmad Tabibi occupies a significant place in classical Turkic literature due to his rich genre repertoire, profound poetic thinking, and high artistic achievement.